PENERAPAN COST VOLUME PROFIT ANALYSIS SEBAGAI ALAT PERENCANAAN PENJUALAN UNTUK MENETAPKAN LABA (STUDI KASUS CV.WIJAYANTI PRESS , MOJOKERTO – JAWA TIMUR) - NUR WIJAYANTI, MIKE (Jurnal Akuntansi AKUNESA, 2018)
This study takes a case study on CV. Wijayanti Press that produces maps, diplomas, report cards cover (hot print), prints, hats, ties, school attributes, and others. In conducting its business, the owners have not applied CV.Wijayanti Press analysis of the calculation of the cost, volume, and profitability. CV.Wijayanti Press can not know the performance of the company due to the unavailability of financial statements, the level of sales and operating profit of the company can not be known with certainty. The purpose of this study to determine the application of cost volume profit analysis as a planning tool to determine the profits. By using quantitative research methods. The results of the research, the product of diploma cover hot folder print in the sales period August - November 2016 requires a sales volume of 2,389 units to reach the break even point, contribution margin 53.56%, margin of safety Rp 1147244920.2, and operating leverage 1.051%. Keywords : cost volume profit analysis, sales, profit